ChemInform Abstract: Asymmetric Synthesis of Amines Through Rhodium‐Catalyzed C—H Amination with Sulfonimidoylnitrenes. Issue 52 (24th December 2013) - Darses, Benjamin; Jarvis, Amanda G.; Mafroud, Abdel‐Kader; Estenne‐Bouhtou, Genevieve; Dargazanli, Gihad; Dauban, Philippe
Abstract An efficient asymmetric C—H amination of benzylic and allylic substrates through catalytic insertion of a chiral nitrene is reported.